PROFESSIONAL TRAINING OF STUDENTS IN THE INTERACTION OF SCHOOL-COLLEGE-UNIVERSITY - Aitenova, Elmira; Әбдіғапбарова, Ұлжарқын; Сматова, Клара; Ризаходжаева, Г.А. (Pedagogy and Psychology, 2022)
The article discusses the psychological and pedagogical aspects of the concepts of activity, professional activity, professional and pedagogical activity, preparation, readiness for pedagogical activity. In our research work, analyzing philosophical, psychological and pedagogical scientific works, we formulate: the professional activity of a future teacher is a set of actions in the performance of educational, methodological, research, social and communicative functions in the subject-subject interaction in the pedagogical process. On the basis of the "school-college-university" interaction, opportunities for the development of professional activities of future teachers are opening up by improving the interaction of school and college, university, cooperation of creatively working school teachers, college teachers and University scientists, continuity of science and education. That is, the conducted analysis suggests that the training of future teachers for professional activity in the conditions of dual-oriented training in the system of higher pedagogical education has now been resumed. After all, as you know, the main requirement is the transition from theory to practice and compliance with modern market demands. For many years, scientists and practitioners have been aware of the importance of the practical component of the professional training process of a future teacher, looking for effective ways to improve it. Today we can say with confidence that dual-oriented training is extremely necessary for the development of the practical part of modern professional training of a future teacher.